Estimation of the Centre of Mass From Motion Capture and Force Plate Recordings: A Study on the Elderly - S. Cotton; M. Vanoncini; P. Fraisse; N. Ramdani; E. Demircan; A. P. Murray; T. Keller (Applied Bionics and Biomechanics)
The estimation of the centre of mass position in humans is usually based on biomechanical models developed from anthropometric tables. This method can potentially introduce errors in studies involving elderly people, since the ageing process is typically associated with a modification of the distribution of the body mass. In this paper, an alternative technique is proposed, and evaluated with an experimental study on 9 elderly volunteers. The technique is based on a virtual chain, identified from experimental data and locating the subject's centre of mass. Its configuration defines the location of the centre of mass, and is a function of the anatomical joint angles measured on the subject. This method is a valuable investigation tool in the field of geronto-technology, since it overcomes some of the problems encountered with other CoM estimation methods.